Transformação de Mobius no Plano Complexo - Bezerra Filho, José Miguel [UNESP] (2013)
In this work, we study the set of complex numbers as points of the plane. We relate this set with the group of symmetric matrices of order 2. Moreover we study some transformations on the plane emphasizing the Mobius Transformation